COPD and acute myocardial infarction - Laurien Goedemans; Jeroen J. Bax; Victoria Delgado (European Respiratory Review, 2020)
COPD is strongly associated with cardiovascular disease, in particular acute myocardial infarction (AMI). Besides shared risk factors, COPD-related factors, such as systemic inflammation and hypoxia, underlie the pathophysiological interaction between COPD and AMI. The prevalence of COPD amongst AMI populations ranges from 7% to 30%, which is possibly even an underestimation due to underdiagnoses of COPD in general. Following the acute event, patients with COPD have an increased risk of mortality, heart failure and arrhythmias during follow-up. Adequate risk stratification can be performed using various imaging techniques, evaluating cardiac size and function after AMI. Conventional imaging techniques such as echocardiography and cardiac magnetic resonance imaging have already indicated impaired cardiac function in patients with COPD without known cardiovascular disease. Advanced imaging techniques such as speckle-tracking echocardiography and T1 mapping could provide more insight into cardiac structure and function after AMI and have proven to be of prognostic value. Future research is required to better understand the impact of AMI on patients with COPD in order to provide effective secondary prevention. The present article summarises the current knowledge on the pathophysiologic factors involved in the interaction between COPD and AMI, the prevalence and outcomes of AMI in patients with COPD and the role of imaging in the acute phase and risk stratification after AMI in patients with COPD.